Studies on Synthesis of Aldimines: Part-I. Synthesis, Characterization and Biological Activity of Aldimines from Benzaldehyde with variedly substituted anilines - Patil, C. J.; Patil, Manisha C.; Patil, Mrunmayee C. (Recent Research in Science and Technology)
A conventional condensation reaction of an aromatic aldehyde, Benzaldehyde with seven different aromatic amines viz. Aniline, 2-Choro-aniline, 3-Choro-aniline, 4-Choro-aniline, 2-Nitro-aniline, 3-Nitro-aniline and 4-Nitro-aniline and reacted efficiently to synthesize a series of Aldmines, I to VII, in moderate to high yield and high purity. The reaction was monitored and the products were analyzed by employing the TLC technique. All the products obtained were characterized by their colour, physical constant, TLC, elemental analysis and spectral (UV-Vis and FTIR) method. The synthesized Aldimines were subjected to in vitro biological activity.